Collaborative Governance Dalam Penanggulangan HIV Dan AIDS Di Kota Denpasar - Marhaeni, Kadek Sri; Prabawati, Ni Putu Anik; Winaya, I Ketut (CITIZEN CHARTER, 2022)
Denpasar is a city that has the highest HIV and AIDS cases in Bali Province. To overcome this problem, the government of Denpasar has implemented a collaborative partnership between the Government, NGOs, and the society. However, the collaboration has been established is still experiencing several obstacles, such as the lack of HIV prevention facilities, the limited quality of NGO support, and the existence of misperceptions in the community that HIV-AIDS is a very dangerous disease. This study aims to determine the application of Collaborative Governance in HIV-AIDS Prevention in Denpasar City. The research method is descriptive qualitative. The analysis uses the theory of success measures according to DeSeve (2007). The findings show that the indicators of networked structure, commitment to a common purpose, trust among the participant, governance, access to authority, distributive accountability/ responsibility have worked well, but indicators information sharing and access to resources is still not optimal. Keywords: Collaborative Governance, Prevention, HIV-AIDS